Sustainable development as the conceptual basis for inclusive physical education in the new Ukrainian school - Semenenko , Viacheslav; Telius , Valeriia; Mospan , Yevgeny (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction. Inclusive education is a fundamental component of Ukraine's sustainable development strategy and a key tool for implementing the UN global goal on quality education. In the context of implementing the New Ukrainian School concept, special emphasis is placed on ensuring equal access to education, overcoming social barriers and creating a safe educational environment for children with special educational needs. The modern educational paradigm is based on a democratic approach and the use of innovative technologies that allow adapting the educational process to the individual trajectories of students, contributing to their successful social integration without discrimination. Of particular importance is the implementation of inclusion within the framework of physical education and the formation of healthy lifestyle competencies. The development of inclusive infrastructure and the professional activities of teachers are aimed at creating comfortable conditions for the cognitive and emotional growth of each child. Applying an activity-based approach and adapting curricula to the needs of individuals with special educational needs are key factors in ensuring social justice and high-quality preparation of young people for life in the face of modern global challenges. The purpose of the study is to investigate the conditions for implementing inclusive education in the process of physical education according to the concept of the New Ukrainian School. Material and methods. The study was conducted on the basis of secondary education institutions in Kyiv and Kyiv region, Ukraine. The study involved 120 physical education teachers who provide the educational process in the context of the implementation of the New Ukrainian School concept. The survey covered specialists working with students of different age groups in blended and full-time forms of education. The study was conducted under martial law, which required special attention to security aspects and adaptation of the inclusive environment to modern challenges. The following methods were used in the study: theoretical analysis and generalization of data from scientific and methodological literature, content analysis of documentary and statistical materials, methods of sociological survey, methods of mathematical statistics. Results. The study substantiated the need to improve the material and technical base and methodological training of teachers for the effective implementation of inclusive education in physical education lessons in the New Ukrainian School. It was found that the adaptation of the educational space and the use of individual development trajectories contribute to ensuring equal access to physical activity and successful social integration of students with special educational needs for the implementation of the UN Sustainable Development Goals. Conclusion. In the context of implementing the sustainable development strategy and implementing the concept of the New Ukrainian School, the issue of transforming physical education on the basis of inclusion is relevant. Creating a barrier-free educational environment and ensuring equal access to physical activity are critically important for the full development and social adaptation of students with special educational needs. The study confirmed that the effective implementation of an inclusive approach in physical education lessons requires a systematic update of the material and technical base and increasing the methodological competence of teachers. The use of adapted programs and individual development trajectories allows not only to improve the physical condition of students, but also to overcome social isolation, forming in children motivation for an active lifestyle and self-confidence regardless of existing nosologies.